Structural, optoelectronic, mechanical and thermodynamic properties of AgMgX3(X= Cl, Br): A first principles study - Md Ashikur Rahman; Md Jobayer Hassan; Jerin Haider; Md Meskat Ali; Md Mahmudul Hasan; Md Alamgir Badsha (Physics Open, 2025)
Maintaining a contamination-free environment is crucial for researchers developing industrial products. The lead-free perovskite compounds, AgMgX3 (X = Cl, Br), have utilized density functional theory (DFT) to assess their properties. The stability of these compounds is confirmed by the Goldsmith tolerance factor and negative formation energy. For AgMgCl3, the calculated indirect band gap values are 1.655 eV and 1.228 eV, while AgMgBr3 shows band gap values of 0.889 eV and 0.453 eV, as determined by the GGA-PBE and LDA-CAPZ functionals, respectively. In addition, the hybrid functional HSE06 yields a band gap of 1.80 eV for AgMgCl3 and 1.035 eV for AgMgBr3. Both materials exhibit p-type semiconductor behavior. Moreover, these compounds demonstrate a high absorption coefficient, good optical conductivity, and low reflectivity within the visible spectral range, making them promising candidates for various applications. Their mechanical stability and ductility support the fabrication of thin films for use in heterostructure devices. The imaginary phonon frequency indicates dynamical instability, and ab initio molecular dynamics (AIMD) reaffirm their elastic stability. Both perovskites exhibit anharmonic behavior at higher temperatures below melting point and high Debye temperatures suggest strong thermal stability. Consequently, the properties of these materials may pave the way for new optoelectronic applications.